2020
DOI: 10.1038/s41386-020-00833-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of eszopiclone on sleep spindles and memory consolidation in schizophrenia: a randomized clinical trial

Abstract: Sleep spindles, defining oscillations of stage 2 non-rapid eye movement sleep (N2), mediate memory consolidation. Schizophrenia is characterized by reduced spindle activity that correlates with impaired sleep-dependent memory consolidation. In a small, randomized, placebo-controlled pilot study of schizophrenia, eszopiclone (Lunesta®), a nonbenzodiazepine sedative hypnotic, increased N2 spindle density (number/minute) but did not significantly improve memory. This larger double-blind crossover study that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 83 publications
8
55
1
Order By: Relevance
“…It is important to note that our findings are correlational in nature. Other work has shown that it is possible to enhance spindle activity pharmacologically to alter memory function, (Kaestner et al, 2013; Niknazar et al, 2015), though potentially at the cost of disrupting slow oscillation-spindle coupling processes (Mylonas et al, 2020). Furthermore, commonly used pharmacological agents such as zolpidem and eszopiclone have been shown to induce widespread alterations in the sleep EEG, and as such do not solely target changes in sleep spindles (Aeschbach et al, 1994; Monti et al, 2000; Struyk et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that our findings are correlational in nature. Other work has shown that it is possible to enhance spindle activity pharmacologically to alter memory function, (Kaestner et al, 2013; Niknazar et al, 2015), though potentially at the cost of disrupting slow oscillation-spindle coupling processes (Mylonas et al, 2020). Furthermore, commonly used pharmacological agents such as zolpidem and eszopiclone have been shown to induce widespread alterations in the sleep EEG, and as such do not solely target changes in sleep spindles (Aeschbach et al, 1994; Monti et al, 2000; Struyk et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to consider that coupling events are just one neurophysiological event that occurs during SWS and is a particularly rare event. Only ~15% of spindles couple to slow oscillations, and coupled spindle density has been reported as being around 0.5 per minute (Denis, Mylonas, et al, 2020;Mylonas et al, 2020). As such, coupling is a rare event in the broader SWS sleep state.…”
Section: Discussionmentioning
confidence: 99%
“…This approach to slow oscillation spindle coupling has been widely used elsewhere (e.g. Staresina et al, 2015;Helfrich et al, 2018;Mylonas et al, 2020). We extracted the percentage of all spindles coupled with a slow oscillation at each electrode, the average phase of the slow oscillation at the peak of each coupled spindle, and the overall coupling strength (mean vector length).…”
Section: Slow Oscillation-spindle Couplingmentioning
confidence: 99%
“…It is important to consider that coupling events are just one neurophysiological event that occurs during SWS and is a particularly rare event. Only ~15% of spindles couple to slow oscillations, and coupled spindle density has been reported as being around 0.5 per minute (Denis, Mylonas, et al , 2020; Mylonas et al , 2020). As such, coupling is a rare event in the broader SWS sleep state.…”
Section: Discussionmentioning
confidence: 99%